PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS PESERTA DIDIK - Lana Khairani Putri; Uswatun Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research and development study aims to address problems in primary school mathematics learning, particularly students' tendency to memorize formulas without deeply understanding the concepts. As a result, students struggle to apply mathematical knowledge in real-life situations. This issue is compounded by instructional materials that are procedural and lack contextual relevance. To overcome this, a Student Worksheet (LKPD) based on the Realistic Mathematics Education (RME) approach was developed, emphasizing contextual learning through real-world experiences.The research was conducted with second-grade students at SDIT Al-Asror Tulungagung, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The LKPD was designed according to RME principles, validated by experts (score: 95%, categorized as highly valid), and tested through a pretest-posttest design. Results showed an increase in students' average scores from 73.75 (pretest) to 94.17 (posttest), indicating a 31.49% improvement.This improvement demonstrates the effectiveness of RME-based LKPD in helping students develop a more meaningful and applicable understanding of mathematical concepts. Furthermore, the visually engaging design and contextual learning activities increased student motivation and participation. Therefore, the developed LKPD offers an innovative solution to enhance mathematics learning in primary education.